Predictors of intention to stay and moderating role of gender among executives in the Malaysian manufacturing organizations - Yong, See Chen; Mohd Rasdi, Roziah; Ismail, Maimunah; Asmuni, Azizan (Human Resource Management Academic Research Society, 2017)
Purpose - The purpose of this paper is to test the influence of pay and compensation, career advancement, performance appraisal, and the moderating roles of gender on intention to stay among executive employees in Malaysian manufacturing organizations. Design/methodology/approach - Research data were collected from a sample of 456 executive employees in Malaysian manufacturing organizations. Structural equation modeling was used to test the influences of organizational-related factors and the moderating role of gender on intention to stay. Findings - The results show that pay and compensation and career advancement are viewed as potential predictors of intention to stay. Gender significantly moderates the relationships between pay and compensation, and intention to stay among executive employees. Originality/value - This paper offers another Asian perception into the predicting factors of intention to stay and its moderating role of gender.